Vertically stable, room temperature storage, one-part, post-cure, thermally conductive silicone
The challenges of existing materials during storage and application are solved by using a portion of the repairable polysilicone position in the thermally conductive contact material, combining polyether and plate-like silicon nitride components, achieving high thermal conductivity, good vertical retention and low decomposition.
Patent Information
- Application Number
- JP2024529326
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-11-29
AI Technical Summary
Some existing repairable thermally conductive contact materials have challenges such as thinning, accurate mixing and low-temperature storage during storage and application, while exhibiting poor vertical retention capabilities in gaps with thicknesses exceeding 0.5mm.
A portion of the repairable polysilicone position, containing polyether components and plate-like silica nitride components, combined with the appropriate SiH/Vi ratio, uses a palladium-based hydrosilylation interface catalyst, and cures the material at the contact surface by heat treatment.
It has achieved storage of materials for more than 6 months in 25°C, with high thermal conductivity, good vertical retention ability and low decomposition force, and is suitable for thermally conductive contact materials with gaps of 1.0 mm or more.
Smart Images

Figure 0007653579000001 
Figure 0007653579000002 
Figure 0007653579000003
Abstract
Description
[Technical field]
[0001] The present invention relates to one-part curable polysiloxane compositions that can be used as thermally conductive interface materials, and the use of such compositions as thermal interface materials. [Background technology]
[0002] As electronic devices become smaller and more powerful, the industry is increasingly demanding thermally conductive materials that are useful for dissipating heat generated by such devices. For example, the telecommunications industry is undergoing a generational shift to 5G networks, which requires small, highly integrated electrical devices and a doubling of power requirements (from 600 watts to 1200 watts). If the heat generated by the high power in the small devices is not efficiently dissipated, the devices will be damaged. Thermally conductive interface materials are often used in electronic devices to thermally couple heat-generating and heat-dissipating components.
[0003] There are different types of thermally conductive interface materials. Thermal putties are pre-cured or non-cured materials that can be formulated into thermally conductive interface materials. The advantage of thermal putties is that there are no concerns about preventing premature curing of the material during storage or handling. The challenges with thermal putties are that they are thick, difficult to dispense, and have poor "vertical stay" in applications with thick gaps (over 0.5 millimeters wide). Vertical stay is a measure of how well the material stays in place versus sliding or sagging vertically when positioned between components and oriented with the gap between the components oriented perpendicular to gravity. Curable thermally conductive interface materials can overcome some of the challenges with thermal putties, but have their own challenges. Two-part curable thermally conductive interface materials contain a system of two reactants that react and cure immediately after mixing. Before curing, they tend to have a relatively low viscosity, making them easier to apply than thermal putties. However, two-part curable thermally conductive interface materials require storage and precise mixing of two reactants just prior to application. Some one-part curable thermally conductive interface materials provide a lower viscosity material for ease of application, and then cure into a thicker material after application. The challenge with one-part curable thermally conductive interface materials is that they must be stored at low temperatures (approximately -18°C) before use to prevent hardening prior to application.
[0004] Storage stable at 25 degrees Celsius (°C) for at least six months as determined by the 25°C Storage Test described herein below, and has a thermal stability of 6 watts / meter as determined by ASTM-5470 using a LONGWIN instrument. * Kelvin (W / m * It would advance the art of thermally conductive materials to provide a one-part, curable composition that has a thermal conductivity of 1.0 K or greater, is highly extrudable, as demonstrated by an extrusion rate of greater than 15 grams per minute (g / min) in the Extrusion Test described below, exhibits crack-free performance in a 1.0 millimeter gap, as demonstrated by no slippage or cracking in the Vertical Stay Test described below, exhibits excellent vertical stay, and has a break down force of less than 0.15 megapascals in the Break Down Force Test described below. Summary of the Invention
[0005] Provided herein are storage stable at 25 degrees Celsius (°C) for at least six months as determined by the 25°C Storage Test described herein below, and have a thermal stability of at least 6 watts / meter as determined by ASTM-5470 using a LONGWIN instrument. * Kelvin (W / m * is a one-part curable composition having a thermal conductivity of greater than 1.0 K, is highly extrudable, as demonstrated by an extrusion rate of greater than 15 grams per minute (g / min) in the Extrusion Test described below, exhibits crack-free performance in a 1.0 millimeter gap, as demonstrated by no slippage or cracking in the Vertical Stay Test described below, exhibits excellent vertical stay, and has a break down force of less than 0.15 megapascals in the Break Down Force Test described below.
[0006] Surprisingly, the present invention contains a polyether component and a platelet boron nitride component to provide vertical staying power. Further, the present invention is the result of discovering the proper ratio of silyl hydride (SiH) groups to vinyl groups (SiH / Vi ratio) to achieve crack-free performance in gaps of 1.0 millimeter or greater.
[0007] In a first aspect, the invention provides a method for producing a silicone polymer comprising: (a) 1.6 to 2.5 weight percent of a vinyl-functional silicone polymer having two or more vinyl groups per molecule; (b) at least one silylhydride-functional polysiloxane crosslinker having at least two silylhydride groups per molecule and present at a concentration such that the molar ratio of silylhydride to vinyl in the composition is in the range of 0.3 to 1.0; and (c) a platinum-based hydrosilylation catalyst encapsulated in a thermoplastic polymer, wherein the thermoplastic polymer has an ASTM D 1024 viscosity at a heating rate of 10° C. over the range of −60 to 200° C. at a heating rate of 10° C. / min. (d) 93.5 to 96 weight percent of thermally conductive filler particles other than platelet-shaped boron nitride particles; (e) 0.2 to 2.5 weight percent of the platelet-shaped boron nitride particles; (f) 0.1 to 1.0 weight percent of a polyether additive selected from any combination of one or more of the group consisting of polyether-based polymers and polyorganosiloxane-polyoxyalkylene copolymers; (g) 0.10 to 5.0 weight percent of a filler treating agent; and (h) 0 to 0.5 weight percent of a cure inhibitor, wherein the weight percentages are based on the weight of the curable composition.
[0008] In a second aspect, the invention is a process of using the composition of the first aspect, comprising applying the composition in contact between two components and then heating the curable composition to a temperature above the glass transition temperature of the thermoplastic polymer encapsulating the platinum catalyst to cure the curable composition while in place between the components.
[0009] The compositions of the present invention are useful as thermally conductive materials between components, such as electronic devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Test methods refer to the test method most recent to the priority date of this document unless a date is given with the test method number. Reference to a test method includes both a reference to the testing society and the test method number. The following test method abbreviations and identifiers apply herein: ASTM refers to ASTM International Methods, EN refers to European Norm, DIN refers to Deutsches Institut fur Normung, ISO refers to the International Organization for Standards, and UL refers to the Underwriters Laboratory.
[0011] Products identified by trade names refer to compositions available under those trade names as of the priority date of this document.
[0012] "Plurality" means two or more. "And / or" means "and, or alternatively." All ranges are inclusive of the endpoints unless otherwise indicated.
[0013] In one aspect, the present invention is a curable composition. The curable composition can undergo a crosslinking reaction ("cure"). In this composition, the crosslinking reaction is a hydrosilylation reaction between a vinyl-functional silicone polymer component and a silyl-hydride (Si-H)-functional polysiloxane crosslinker.
[0014] The vinyl functional silicone polymer contains, on average, two or more vinyl groups per molecule. Although any such vinyl functional silicone polymer should work, it is preferred that the vinyl functional silicone polymer contains two or more terminal vinyl groups. Desirably, the vinyl functional silicone polymer has the average chemical structure (I) shown below: R x Vi (3-x) SiO-(R 2 SiO) d -SiR y Vi (3-y) (I) During the ceremony, R is independently selected from alkyl and aryl groups having 1 to 6 carbon atoms at each occurrence. The R group can have 1 or more carbons, 2 or more carbons, 3 or more carbons, 4 or more carbons, or even 5 or more carbons, while having 6 or less carbons, 5 or less carbons, 4 or less carbons, 3 or less carbons, or even 2 or less carbons. Desirably, the R group is independently selected at each occurrence from methyl and phenyl groups. Vi is a vinyl group (-CH=CH 2 ). The subscripts x and y indicate the average number of terminal R groups on either end, each being independently selected from a range of values from 0 to 2 at each occurrence. The average value of x and y may be independently 0 or greater, or even 1 or greater, at each occurrence, and may simultaneously be 2 or less, or even less than 1. The value of x may be equal to the value of y. Desirably, both x and y are 2 at each occurrence. The subscript d stands for (R 2 SiO) groups, and is 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 120 or more, 140 or more, 160 or more, 180 or more, 200 or more, 220 or more, 240 or more, 260 or more, 280 or more, 300 or more, 320 or more, 340 or more, 360 or more, 380 or more, 400 or more, or even 450 or more, and has an average value of 500 or less, 480 or less, 460 or less, 440 or less, 420 or less, 400 or less, 380 or less, 360 or less, 340 or less, 320 or less, 300 or less, 280 or less, 260 or less, 240 or less, 240 or less, 220 or less, 200 or less, 180 or less, 160 or less, 140 or less, 120 or less, 100 or less, 80 or less, 60 or less, or even 40 or less.
[0015] The concentration of the vinyl functional polysiloxane is desirably 1.5 weight percent (wt%) or more, preferably 1.6 wt% or more, 1.7 wt% or more, 1.8 wt% or more, 1.9 wt% or more, 2.0 wt% or more, 2.1 wt% or more, 2.2 wt% or more, 2.3 wt% or more, or even 2.4 wt%, based on the weight of the curable composition, while typically being 2.5 wt% or less, and 2.4 wt% or less, 2.3 wt% or less, 2.2 wt% or less, 2.1 wt% or less, 2.0 wt% or less, 1.9 wt% or less, 1.8 wt% or less, or even 1.7 wt% or less.
[0016] Silylhydride functional polysiloxane crosslinkers contain at least two silylhydride (SiH) groups per molecule. The silylhydride groups can be pendant, terminal, or a combination of both pendant and terminal. A "terminal" group is on a terminal siloxane group of the molecule. A "terminal" siloxane group is bonded to only one other siloxane group. A "pendant" group is on an internal siloxane group of the molecule (a siloxane group bonded to at least two other siloxane groups). A "siloxane group" is a group containing SiO that is bonded to another Si through an oxygen of the SiO. Desirably, the silylhydride functional polysiloxane crosslinker has the average chemical structure (II) shown below: R (3-h) H h SiO-(HRSiO) a -(R 2 SiO) b -SiH h’ R (3-h’) (II) During the ceremony, R at each occurrence is independently selected from alkyl groups and aryl groups having 1 to 6 carbon atoms. The R group can have 1 or more carbons, 2 or more carbons, 3 or more carbons, 4 or more carbons, or even 5 or more carbons, while at the same time having 6 or less carbons, 5 or less carbons, 4 or less carbons, 3 or less carbons, or even 2 or less carbons. Desirably, the R group at each occurrence is independently selected from methyl and phenyl groups. H is a hydrogen atom. The subscripts h and h' refer to the average number of terminal hydrogen atoms at either end, each independently selected from a value ranging from 0 to 3 at each occurrence, provided that the combination of a, h, and h' is at least 2. Preferably, h and h' are independently, at each occurrence, 0 or more, 1 or more, or even 2 or more, and simultaneously 3 or less, 2 or less, or even 1 or less. More preferably, h and h' have the same value. Most preferably, h and h' are both 0. The subscript a is the average number of (HRSiO) groups per molecule. If h and h' are both 0, then a is 2 or greater. If h and h' are not both 0, then subscript a can be 0, provided that the combination of a, h, and h' is at least 2. Preferably, subscript a is 1 or greater, and may be 2 or greater, 3 or greater, 4 or greater, 5 or greater, 6 or greater, 7 or greater, 8 or greater, or even 9 or greater, while typically being 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less. The subscript b represents the (R 2 is the average number of SiO) groups. In general, the subscript b is 5 or more, 10 or more, 20 or more, 25 or more, 30 or more, 40 or more, 50 or more, and may be 75 or more, 100 or more, 125 or more, 150 or more, 175 or more, or even 190 or more, while typically being 200 or less, 175 or less, 150 or less, 125 or less, 100 or less, 75 or less, 50 or less, 40 or less, 30 or less, or even 25 or less, or even 20 or less.
[0017] For example, the silylhydride functional polysiloxane crosslinker can have the following average chemical structure: (CH 3 ) 3 SiO-[Si(CH 3 ) 2 O] 25 -[Si(CH 3 )HO] 2 Si(CH 3 ) 3 .
[0018] The concentration of the silylhydride functional polysiloxane crosslinker is sufficient to provide a molar ratio of silylhydride groups to vinyl groups (SiH / Vi) that is desirably 0.3 or more, and may be 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, and at the same time desirably 1.0 or less, 0.95 or less, 0.85 or less, 0.75 or less, 0.65 or less, 0.55 or less, 0.45 or less, or even 0.35 or less. Surprisingly, it has been discovered that when the curable composition has a SiH / Vi ratio in this range, the composition cures and remains crack-free in a 1.0 millimeter gap in the vertical stay test described below. The value of SiH / Vi is determined by nuclear magnetic resonance spectroscopy.
[0019] The curable composition further comprises a platinum-based hydrosilylation catalyst encapsulated in the thermoplastic polymer. The platinum-based hydrosilylation catalyst can be any useful in hydrosilylation chemistry. Platinum-based hydrosilylation catalysts include platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Karstedt's catalyst), H 2 PtCl 6 , di-μ.-carbonyl-di-.π.-cyclopentadienyldinickel, platinum-carbonyl complexes, platinum-divinyltetramethyldisiloxane complexes, platinum cyclovinylmethylsiloxane complexes, platinum acetylacetonate (acac), platinum black, platinum compounds such as chloroplatinic acid, chloroplatinic acid hexahydrate, reaction products of chloroplatinic acid with monohydric alcohols, platinum bis(ethylacetoacetate), platinum bis(acetylacetonate), and platinum dichloride, can be used as the platinum complexes.
[0020] The thermoplastic polymer encapsulating the platinum-based hydrosilylation catalyst has a glass transition temperature (Tg) in the range of 60 to 80 degrees Celsius (°C). Preferably, the glass transition temperature of the thermoplastic polymer is 60°C or higher, and can be 62°C or higher, 64°C or higher, 66°C or higher, 68°C or higher, 70°C or higher, 72°C or higher, 74°C or higher, 76°C or higher, or even 78°C or higher, but at the same time, it is generally 80°C or lower, and can be 78°C or lower, 76°C or lower, 74°C or lower, 72°C or lower, 70°C or lower, 68°C or lower, 66°C or lower, 64°C or lower, or even 62°C or lower. The Tg of the thermoplastic polymer is 60°C or higher even at higher temperatures than typical room temperature (approximately 25°C) and temperatures for warmer climates and storage conditions to hide the catalyst from the vinyl functional polymer and the silylhydride functional polysiloxane crosslinker, thereby inhibiting catalyzed hydrosilylation crosslinking at room temperature. Above the Tg of a thermoplastic polymer, the polymer softens, exposing the hydrosilylation catalyst and allowing it to catalyze hydrosilylation crosslinking. Determine the Tg of a thermoplastic polymer by differential scanning calorimetry (DSC) according to ASTM D7426 over a temperature ramp from -60 to 200 °C at a heating rate of 10 °C / min to determine the endothermic glass transition temperature (Tg).
[0021] The concentration of the platinum-based hydrosilylation catalyst desirably is sufficient to provide a platinum concentration in the range of 0.1 to 50 parts per million (ppm) by weight, based on the weight of the curable composition. The concentration of the platinum based hydrosilylation catalyst may be that which provides a platinum concentration, in ppm by weight of the curable composition, of at least 0.1 ppm, at least 0.2 ppm, at least 0.3 ppm, at least 0.4 ppm, at least 0.5 ppm, at least 0.6 ppm, at least 0.7 ppm, at least 0.8 ppm, at least 0.9 ppm, at least 1.0 ppm, at least 5.0 ppm, at least 10 ppm, at least 15 ppm, at least 20 ppm, at least 25 ppm, at least 30 ppm, at least 35 ppm, at least 40 ppm, or even at least 45 ppm, while typically at most 50 ppm, or even at most 45 ppm, at most 40 ppm, at most 35 ppm, at most 30 ppm, at most 25 ppm, at most 20 ppm, at most 15 ppm, at most 10 ppm, at most 5.0 ppm, or even at most 1.0 ppm.
[0022] The curable composition further comprises platelet-shaped boron nitride particles. Platelet-shaped boron nitride particles have a plate-like shape that is much thinner than the width or length. Typically, the thickness is 0.5 micrometers or more, preferably 1 micrometers or more, 2 micrometers or more, 3 micrometers or more, 4 micrometers or more, or even 5 micrometers or more, while the thickness is typically 20 micrometers or less, even 15 micrometers or less, or 10 micrometers or less. At the same time, the average of the width and length dimensions is typically 100 micrometers or less, even 80 micrometers or less, 60 micrometers or less, 50 micrometers or less, even 45 micrometers or less, or 40 micrometers or less, while usually 35 micrometers or more, or even 40 micrometers or more.
[0023] The platelet-shaped boron nitride particles function as both a thermally conductive filler and a filler, while the platelet shape contributes to the vertical staying power of the curable composition. The concentration of the platelet-shaped boron nitride particles in the curable composition is typically 0.2 wt% or more, preferably 0.3 wt% or more, 0.4 wt% or more, or even 0.5 wt% or more, and at the same time is typically 2.5 wt% or less, even 2.0 wt% or less, 1.5 wt% or less, 1.0 wt% or less, 0.8 wt% or less, even 0.6 wt% or less, or 0.5 wt% or less, based on the weight of the curable composition.
[0024] The curable composition further comprises thermally conductive filler particles other than platelet-shaped boron nitride particles. All of the thermally conductive filler particles help contribute to increasing the thermal conductivity through the curable composition before and after curing of the curable composition. The thermally conductive filler particles other than platelet-shaped boron nitride particles can comprise any one or combination of two or more of the thermally conductive filler particles useful in thermal interface materials, including aluminum oxide ("alumina") particles, zinc oxide (ZnO) particles, aluminum nitride (AlN) particles, silicon carbide, magnesium oxide, aluminum trihydrate, graphite, carbon fiber, and graphene.
[0025] To facilitate high particle loading in the curable composition, it may be desirable to use a combination of thermally conductive filler particles of different sizes. For example, the thermally conductive filler particles other than platelet-shaped boron nitride particles can include thermally conductive filler particles of two different average sizes, three different average sizes, four different average sizes, or more. For example, the thermally conductive filler particles other than platelet-shaped boron nitride particles can be a combination of particles having three different particle ranges of average particle size, such as 75-100 micrometers, 20-50 micrometers, and less than 10 micrometers.
[0026] The average particle size of the thermally conductive filler particles is determined as the volume weighted median (Dv50) of the particle size distribution of the polyorganosiloxane using a Mastersizer™ 3000 laser diffraction particle size analyzer manufactured by Malvern Instruments.
[0027] Thermally conductive filler particles other than platelet-shaped boron nitride particles are present in a concentration, based on the weight of the curable composition, of 93 wt% or more, preferably 93.5 wt% or more, 94 wt% or more, 94.5 wt% or more, 95 wt% or more, or even 95.5 wt% or more, while typically being present in a concentration of 96.5 wt% or less, or even 96 wt% or less, and can be 95.5 wt% or less, or even 95 wt% or less.
[0028] Thermally conductive filler particles other than aluminum oxide can be present in a concentration of 20% or more, and even 25% or more, by weight based on the weight of the hardenable composition.
[0029] Preferably, the thermally conductive filler particles other than platelet-shaped boron nitride are selected from the group consisting of spherical aluminum oxide having a Dv50 of 90 micrometers, circular aluminum oxide having a Dv50 of 35 micrometers, irregular aluminum oxide having a Dv50 of 2 micrometers, irregular zinc oxide having a Dv50 of 0.11-0.13 micrometers, spherical aluminum nitride having a Dv50 of 80 micrometers, and spherical aluminum oxide having a Dv50 of 2 micrometers. The thermally conductive filler particles other than boron nitride are most preferably selected from the group consisting of (i) 30-31 wt.% spherical aluminum oxide having a Dv50 of 90 micrometers, 29.0-29.3 wt.% circular aluminum oxide having a Dv50 of 35 micrometers, and 23.0-23.3 wt.% irregular Al oxide having a Dv50 of 2 μm. 2 O 3 and (ii) 16.9 wt.% of irregular ZnO having a Dv50 of 0.11-0.13 μm, 48.3-48.4 wt.% of spherical AlN having a Dv50 of 80 μm, and 30.2-30.3 wt.% of spherical AlN having a Dv50 of 2 μm. 2 O 3 and combinations of: and, wherein the weight percentages are based on the weight of the hardenable composition.
[0030] The curable composition further comprises a polyether additive. Surprisingly, the polyether additive provides the curable composition with improved vertical retention when tested in the Vertical Retention Test described below. The polyether additive is any one, or any combination, or two or more, of polyether additives selected from the group consisting of polyether-based polymers and polyorganosiloxane-polyoxyalkylene copolymers. Polyether-based polymers include polyethylene glycol, polypropylene glycol, polypropylene / polyethylene glycol copolymers. Polyorganosiloxane-polyoxyalkylene copolymers include trimethylsiloxy-terminated dimethylsiloxane-[propylene oxide / ethylene oxide] copolymers, such as those having the average chemical structure (III) shown below: (CH 3 ) 3 SiO-[(CH 3 )ASiO] m -[(CH 3 ) 2 SiO] n -Si(CH 3 ) 3 (III) During the ceremony, A is -(CH 2 CH 2 O) p -(CH 2 CH(CH 3 )O) q -CH 3 where: The subscript p has an average value of 10 or greater, and can be preferably 12 or greater, 14 or greater, 16 or greater, or even 18 or greater, and at the same time 20 or less, and can be 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, or even 11 or less; The subscript q has an average value of 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 11 or more, 12 or more, 13 or more, 14 or more, 15 or more, 16 or more, 17 or more, or even 18 or more, and at the same time, can be 20 or less, 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, or 5 or less; The subscript m has an average value of 4 or greater, and can be 5 or greater, 6 or greater, 7 or greater, 8 or greater, 9 or greater, 10 or greater, 11 or greater, 12 or greater, 13 or greater, 14 or greater, 15 or greater, while typically being 16 or less, or even 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, or even 5 or less; The subscript n has an average value of 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 10 or more, 12 or more, 14 or more, 16 or more, 18 or more, 20 or more, 24 or more, 26 or more, 30 or more, 35 or more, or even 40 or more, while typically being 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, or even 10 or less.
[0031] Desirably, the curable composition comprises one or more trimethylsiloxy-terminated dimethylsiloxane-[propylene oxide / ethylene oxide] copolymers.
[0032] The concentration of the polyether additive is desirably 0.1% by weight or more, even 0.2% by weight or more, 0.3% by weight or more, 0.4% by weight or more, 0.5% by weight or more, 0.6% by weight or more, 0.7% by weight or more, 0.8% by weight or more, or even 0.9% by weight, and at the same time is typically 1.0% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.6% by weight or less, 0.5% by weight or less, 0.4% by weight or less, 0.3% by weight or less, or even 0.2% by weight or less, in weight % based on the weight of the curable composition. When the concentration of the polyether additive is within these ranges, it contributes to the vertical staying property of the curable composition.
[0033] The curable composition may further include, and preferably further includes, a cure inhibitor. The cure inhibitor can help prevent premature curing of the curable composition. Examples of suitable cure inhibitors include any one or any combination of two or more selected from methyl(tris(1,1-dimethyl-2-propynyloxy))silane; methylvinylcyclosiloxane, methylbutynol; 3,5-dimethyl-1-hexyn-3-ol; ethynylcyclohexanol; and phenylbutynol. The concentration of the cure inhibitor, in weight percent relative to the weight of the curable composition, is 0 wt.% or more, 0.01 wt.% or more, 0.02 wt.% or more, 0.03 wt.% or more, 0.04 wt.% or more, 0.05 wt.% or more, 0.07 wt.% or more, 0.1 wt.% or more, 0.12 wt.% or more, 0.14 wt.% or more, 0.16 wt.% or more, 0.18 wt.% or more, 0.20 wt.% or more, 0.25 wt.% or more, 0.30 wt.% or more, 0.35 wt.% or more, 0.40 wt.% or more, or even 0.45 wt.% or more, while typically being 0.5 wt.% or less, or even 0.4 wt.% or less, 0.3 wt.% or less, 0.2 wt.% or less, 0.1 wt.% or less, or even 0.05 wt.% or less, 0.04 wt.% or less, or even 0.03 wt.% or less.
[0034] The curable composition can, and desirably, further comprise a filler treating agent. The filler treating agent is typically a trialkoxysilyl compound, which is a-Si(OR) 3 A compound comprising a group, wherein each R at each occurrence is independently an alkyl group having 1 or more carbons, 2 or more carbons, 3 or more carbons, 4 or more carbons, or even 5 or more carbons, while having 6 or less carbons, 5 or less carbons, 4 or less carbons, 3 or less carbons, or even 2 or less carbons. Desirably, each R group is methyl. Desirably, the filler treating agent is one or any combination of two or more components selected from the group consisting of alkyltrialkoxysilanes and monotrialkoxysiloxy-terminated diorganopolysiloxanes.
[0035] Suitable alkyltrialkoxysilanes include those having the formula R a (Rb O) 3 Si, wherein R a and R b Each of R is independently, at each occurrence, 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, or even 11 or more carbon atoms, while typically containing up to 20, up to 18, up to 16, up to 14, up to 12 carbon atoms, and may contain up to 10 carbon atoms. b is preferably methyl so as to form a methoxyl group bonded to the silicon atom. A particularly preferred alkyltrialkoxysilane is n-decyltrimethoxysilane.
[0036] Suitable monotrialkoxysiloxy-terminated diorganopolysiloxanes include those having the average formula R c 3 SiO[R d 2 SiO] g SiOR e 3 wherein each R c , R d and R e is independently selected from hydrocarbyls which, in each occurrence, have 1 or more carbon atoms, and can have 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or even 8 or more carbon atoms, while typically containing 10 or less, 8 or less, 6 or less, 4 or less, or even 2 or less carbon atoms, and the subscript g typically has a value of 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, or even 110 or more, while typically having a value of 200 or less, 150 or less, 125 or less, 120 or less, or even 110 or less. Particularly desirable monotrialkoxysiloxy-terminated diorganopolysiloxanes have the average chemical formula (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] 110 Si(OCH 3 ) 3 has.
[0037] For example, the curable composition may comprise n-decyltrimethoxysilane and (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] 110 Si(OCH 3 ) 3 may include any one or any combination of:
[0038] The concentration of the filler treating agent, in weight % based on the weight of the curable composition, can be 0 wt% or more, 0.10 wt% or more, 0.20 wt% or more, 0.30 wt% or more, 0.40 wt% or more, 0.50 wt% or more, 0.60 wt% or more, 0.70 wt% or more, 0.80 wt% or more, 0.90 wt% or more, 1.00 wt% or more, 1.25 wt% or more, 1.50 wt% or more, 1.60 wt% or more, while typically being present at a concentration of 5.0 wt% or less, and can be 4.0 wt% or less, 3.0 wt% or less, 2.0 wt% or less, 1.75 wt% or less, 1.70 wt% or less, or even 1.65 wt% or less.
[0039] The curable composition may further comprise or not comprise any combination of any one or more of additional additives such as silica, fumed silica, pigments, carbon black, antioxidants, and glass beads. For example, the curable composition may comprise fumed silica at a concentration of 0% by weight or more, or even 0.01% by weight or more, 0.02% by weight or more, 0.03% by weight or more, 0.04% by weight or more, or even 0.05% by weight or more, while typically at a concentration of 0.20% by weight or less, 0.15% by weight or less, 0.10% by weight or less, 0.08% by weight or less, or 0.06% by weight or less, based on the weight of the curable composition. Additionally, or alternatively, the composition may include a pigment such as copper phthalocyanine powder in a concentration, based on the weight of the curable composition, of 0.05 wt.% or more, 0.08 wt.% or more, 0.10 wt.% or more, or even 0.12 wt.% or more, while typically in a concentration of 0.5 wt.% or less, 0.4 wt.% or less, 0.3 wt.% or less, 0.2 wt.% or less, or even 0.15 wt.% or less.
[0040] The curable composition of the present invention is useful as a thermal interface material that can be applied between components and cured in place between the components. In this regard, the present invention may be a process for using the curable composition, which includes applying the composition in contact between two or more components and then heating the curable composition to a temperature above the Tg of the thermoplastic polymer encapsulating the platinum catalyst to cure the curable composition while in place between the components. The curable composition is particularly valuable as a thermal interface material in gaps of 1 millimeter or more between components, since it cures into a crack-free cured composition even in gaps of 1 millimeter. Thus, the process of the present invention may include applying the curable composition to a thickness of 1 millimeter or more, the thickness corresponding to the dimension of the composition extending between the two components (i.e., the width of the gap between the components). EXAMPLES
[0041] Table 1 lists the components used in the preparation of the examples (Examples) and comparative examples (Comparative Examples) described below. The components are identified in Table 1 by the following abbreviations: vinyl functional silicone polymer ("VP"), silylhydride functional polysiloxane ("XL"), platinum based hydrosilylation catalyst ("Pt catalyst"), platelet-shaped boron nitride particles ("BN particles"), thermally conductive filler ("TC filler"), polyether additive ("PE additive"), filler treating agent ("TA"), and "Vi" stands for vinyl (-CH=CH 2 ) group. PolarTherm is a trademark of Momentive Performance Materials Quartz, Inc. Alunabeads is a trademark of Showa Denko KK Aerosil is a trademark of Evonik Operations GMBH DOWFAX is a trademark of The Dow Chemical Company.
[0042] [Table 1-1]
[0043] [Table 1-2]
[0044] Sample preparation The Examples and Comparative Examples are prepared as follows using a 4 liter Sigma blade kneader mixer with the formulation ingredients listed in Table 2 (Comparative) and Table 3 (Example), which list the ingredients in weight % based on the weight of the curable composition.
[0045] Place the specified amounts of VP, TA, and pigment ingredients into the mixer and mix for 5 minutes at 20 revolutions per minute (RPM) under a nitrogen flow of 0.4 cubic meters / hour. Add additional Filler 1 and TC Filler 4 while mixing and continue mixing for 10 minutes (min) at 45 RPM under nitrogen purge. Add TC Filler 3 and mix for 10 minutes at 45 RPM under nitrogen purge. Stop mixing and scrape material from walls of mixing vessel and cover. Add TC Filler 2 and mix for 10 minutes at 30 RPM under nitrogen purge. Add TC Filler 1 and mix for 10 minutes at 30 RPM under nitrogen purge. Stop mixing and scrape material from walls of mixing vessel. Continue mixing at 30 RPM under vacuum and heat to 130°C for 40 minutes. Cool to 40°C, stop mixing and release vacuum. Scrape material from walls of vessel and mixer blades. Add cure inhibitor 1, XL1, and PE additive and mix at 30 RPM for 15 minutes, then 15 minutes under nitrogen purge. Cool to 25°C, add BN particles and Pt catalyst component to mixer and mix at 30 RPM for 45 minutes under nitrogen purge. Continue mixing at 30 RPM for 20 minutes with full vacuum. Stop mixing and release vacuum to obtain thermal composition for corresponding comparative example or example.
[0046] Sample characterization The following test procedures are used to characterize the Comparative and Examples for storage stability at 25° C., extrudability, vertical stay (1.5 mm thickness), crack formation (1.0 mm thickness), thermal conductivity, and decomposition force. The results are shown in Table 4 (Comparative) and Table 5 (Example). The results are reported as a value and whether the sample passed (P) or failed (F) the characterization test.
[0047] 25° C. Storage Test. Place approximately 120 grams of sample material in a 30 milliliter EFT syringe. Close the syringe and store at 25° C. for six months. After six months, test the sample for extrudability in an Extrusion Test. If the extrusion rate is less than 5 grams per minute (g / min), the sample fails the 25° C. Storage Test.
[0048] Extrusion Test. A 30 milliliter EFD plastic cartridge without a tip is filled with the sample composition. The sample composition is dispensed under a pressure of 621 kilopascals (90 pounds per square inch) and the mass of sample composition extruded in one minute is recorded. The test is repeated five times and the average amount extruded in one minute is determined to obtain the extrusion rate of the sample composition in grams per minute (g / min). A sample passes if it achieves an extrusion rate of at least 15 g / min.
[0049] Thermal Conductivity. Determine the thermal conductivity of the specimens according to ASTM-5470 using a Lon Gwin Model LW 9389 TIM Thermal Resistance and Conductivity Measurement Apparatus. The test time is 15 minutes per specimen and the temperature is 80°C. A minimum of 6 watts / meter * Passes thermal conductivity in Kelvin.
[0050] Vertical Stay Test (and Crack Formation Evaluation): A 1.5mm variation of this test is used to determine vertical stay and a 1.0mm variation of this test is used to determine if it has crack-free performance at a 1.0mm gap.
[0051] For vertical stay, 0.9 milliliters (mL) of sample is dispensed onto the center of the surface of an aluminum plate. A 1.5 mm thick spacer is placed on either side of the sample, then a clear glass plate is applied over the sample to squeeze the sample to a thickness of 1.5 mm, fixing the aluminum plate to the glass plate. The sample is outlined on the glass plate and its original position is marked. The assembly is oriented so that the plates and the space between them are oriented perpendicular to the Earth's gravity, with 1.5 mm spacers on either side of the sample, and there is free space above and below the sample. The assembly is cycled from -10°C to 90°C with a program of maintaining -10°C for 30 minutes, then heating to 90°C in 30 minutes, maintaining 90°C for 30 minutes, then decreasing to -10°C in 30 minutes. This cycle is repeated for 1,000 hours. Finally, the position of the sample material between the plates is observed. If the sample falls more than 10% in place, the test is failed.
[0052] The test is repeated using a 0.6 mL sample and a 1.0 mm thick spacer and evaluated for cracks. Observe after 1,000 hours of thermal cycling to determine if there are any visible cracks in the sample. The sample passes if there are no visible cracks.
[0053] Disintegration Force Test. The disintegration force of a sample is determined by applying a sample to a depth of more than 1 millimeter (mm) to the center of a piece of nickel plate 25 mm wide by 75 mm long. A 1 mm thick spacer is placed on either side of the sample and an aluminum plate 25 mm wide by 75 mm long is pressed onto the sample oriented perpendicular to the nickel plate. The aluminum plate is pressed against the nickel plate compressing the sample between the two plates to a thickness of 1 mm thick and 25 mm square. The plates and sample are heated to 100°C for 24 hours and then allowed to cool to 25°C. A texture analyzer (TA XT plus from Lotun Science Company, Ltd) using a P1 probe is used to measure the force required to separate the plates by pulling the plate apart in a direction perpendicular to the plates, directly above the bonded portion of the plates, at a speed of 50.8 millimeters per minute. The maximum amount of force required to separate the metal plates corresponds to the disintegration force of the sample. A disintegration force of 0.15 megapascals (MPa) or less is required to pass the disintegration force test.
[0054] [Table 2]
[0055] [Table 3]
[0056] [Table 4]
[0057] [Table 5]
[0058] The results in Table 5 show that the composition of the present invention solves all of the problems described below: is storage stable at 25 degrees Celsius (°C) for at least six months as determined by the 25°C storage stability test, and has a thermal conductivity of 6 watts / meter as determined by ASTM-5470 using a LONGWIN instrument. * Kelvin (W / m * 1. A one-part curable composition having a thermal conductivity of greater than or equal to 1.0 K, being highly extrudable as demonstrated by an extrusion rate of greater than 15 grams per minute (g / min) in an Extrusion Test, exhibiting crack-free performance and excellent vertical stay at a 1.0 millimeter gap as demonstrated by no slippage or cracking in a Vertical Stay Test, and having a break down force of less than 0.15 megapascals in a Break Down Force Test.
[0059] In contrast, Table 4 shows that compositions that deviate from one or more of the requirements of the compositions of the present invention do not solve all of these problems.
Claims
1. 1. A curable composition comprising: (a) 1.6 to 2.5 weight percent of a vinyl-functional silicone polymer having two or more vinyl groups per molecule; (b) at least one silyl hydride functional polysiloxane crosslinker having at least two silyl hydride groups per molecule and present in a concentration such that the molar ratio of silyl hydride groups to vinyl groups in the composition ranges from 0.3 to 1.0; (c) a platinum-based hydrosilylation catalyst encapsulated in a thermoplastic polymer, the thermoplastic polymer having a glass transition temperature in the range of 60-80° C. as measured by ASTM D7426 over the range of −60 to 200° C. at a heating rate of 10° C. / min; (d) 93.5 to 96 weight percent thermally conductive filler particles other than platelet-shaped boron nitride particles; (e) 0.2 to 2.5 weight percent platelet-shaped boron nitride particles; (f) 0.1 to 1.0 weight percent of a polyether additive selected from one or any combination of one or more of the group consisting of polyether-based polymers and polyorganosiloxane-polyoxyalkylene copolymers; (g) 0.10 to 5.0 weight percent of a filler treating agent; (h) 0 to 0.5 weight percent of a cure inhibitor; wherein the weight percentages are based on the weight of the curable composition, and the platelet-shaped boron nitride particles have an average thickness of 0.5 to 20 micrometers, and average width and length dimensions of 35 to 100 micrometers.
2. The vinyl functional silicone polymer has the following average chemical structure (I): R x Vi (3-x) SiO-(R 2 SiO) d -SiR y Vi (3-y) (I) where R, at each occurrence, is independently selected from alkyl and aryl groups having 1 to 6 carbon atoms; Vi is a vinyl group; x and y represent the average number of terminal R groups at either end, each independently selected at each occurrence from a value ranging from 0 to 2; and d is (R 2 2. The composition of claim 1, wherein said SiO group has an average number of groups greater than or equal to 30 and less than or equal to 500.
3. The silylhydride functional polysiloxane crosslinker has the following average chemical structure (II): R (3-h) H h SiO-(HRSiO) a -(R 2 SiO) b -SiH h’ R (3-h’) (II) wherein R is each independently selected from alkyl and aryl groups having 1 to 6 carbon atoms; H is a hydrogen atom; h and h' refer to the average number of terminal hydrogen atoms at either end and are each independently selected from a value ranging from 0 to 3; subscript a is the average number of (HRSiO) groups per molecule and has a value ranging from 0 to 10; h, h', and a are selected such that the sum of h, h', and a is 2 or greater; and subscript b represents the average number of (R 2 The composition according to claim 1 or 2, wherein the average number of (SiO) groups is in the range of 5 to 200.
4. 4. The composition of claim 1, wherein the polyether additive is selected from one or any combination of one or more of the group consisting of polypropylene glycol, polypropylene / polyethylene glycol copolymer, and trimethylsiloxy-terminated dimethylsiloxane-[propylene oxide / ethylene oxide] copolymer.
5. The trimethylsiloxy-terminated dimethylsiloxane-[propylene oxide / ethylene oxide] copolymer is selected from those having the following average chemical structure (III): (CH) 3 ) 3 SiO-[(CH 3 )ASiO] m -[(CH 3 ) 2 Yes) n -Yes (CH) 3 ) 3 (III) A is -(CH 2 CH 2 O) p - (CH 2 CH (CH 3 ) O) q -CH 3 5. The composition of claim 4, wherein p has an average value of 10 to 20, q has an average value of 4 to 20, m has an average value of 4 to 16, and n has an average value of 4 to 50.
6. The composition of claim 1, wherein the thermally conductive filler particles of the composition other than the platelet-shaped boron nitride are selected from the group consisting of spherical aluminum oxide having a Dv50 of 90 micrometers, circular aluminum oxide having a Dv50 of 35 micrometers, irregular aluminum oxide having a Dv50 of 2 micrometers, irregular zinc oxide having a Dv50 of 0.11 to 0.13 micrometers, spherical aluminum nitride having a Dv50 of 80 micrometers, and spherical aluminum oxide having a Dv50 of 2 micrometers.
7. The composition of any one of claims 1 to 6, wherein the filler treating agent is any one or any combination of one or more of the compositions selected from the group consisting of alkyltrialkoxysilanes and monotrialkoxysiloxy terminated diorganopolysiloxanes.
8. The composition of any one of claims 1 to 7, further comprising any one or any combination of one or more additional additives selected from the group consisting of fumed silica and pigments.
9. 13. A process for using the composition of claim 1 comprising applying the composition in contact between two compositions and then heating the curable composition to a temperature above the glass transition temperature of the thermoplastic polymer encapsulating the platinum catalyst to cure the curable composition while in place between the compositions.
10. 10. The process of claim 9, wherein the composition of claim 1 has a thickness of 1 millimeter or more, said thickness being the dimension of the composition extending between the two compositions.
Citation Information
Patent Citations
Preparation of thermally plastic resin fine particles containing catalyst for hydrosilylation reaction
JP1992029748A
Heat-conductive silicone rubber composition
JP1996319425A
Thermally conductive silicone elastomer composition
JP2004168920A
Silicone composition and thermally conductive cured silicone product
JP2004533515A
Trialkoxy-functional branched siloxane compositions
JP2022548808A